Physical fitness of urban and rural schoolchildren from low social strata in Yucatan, Mexico - Aftanasiuk, Maryla (Studia Ecologiae et Bioethicae, 2003)
Body build and physical fitness of schoolchildren of low socioeconomic strata from urban and rural areas of Yucatan were studied. The material consisted of 552 children from Merida (the capital city of Yucatan State, Mexico) and of 526 children from the Yaxcaba horticultural community, 7 through 14 years of age. These are cross-sectional samples studied in 1996-97 in Merida and in 1999 and 2000 in Yaxcaba. The ethnic origin was evaluated using two surnames of children (from the father and mother side). The studied variables included stature, BMI, arm circumference, grip strength, agility run, Sargent vertical jump index (explosive strength), spine flexibility index, and reaction time. Urban children are significantly taller than rural ones, and BMI and arm circumference show also a tendency to be greater in urban areas. Physical fitness tests are better performed (better results) in rural areas than in urban ones. If the whole material is divided according to two ethnic groups (Mayas and Mestizos, and Creoles) the differences in body build are still observed but those in physical fitness disappeared. Creole children are taller than Mayas and Mestizos and they show a tendency to have more weight for height and greater arm circumference. Generally, the differences in physical fitness are only observed between rural and urban children what may be caused by a more active way of life in villages than in towns resulting from agricultural activity. However, differences in stature are observed between ethnic as well as between rural and urban groups. This may have the genetic origin (Creoles and Mayas), and in the case of different localities, it may also be caused by more various nutrition in towns than in villages.